Valdymo sferos informacijos vartotojų reikmių tyrimo metodikos klausimai - Dambrauskaitė, Aldona; Kancleris, Algirdas; Vladimirovas, Levas (Knygotyra, 1976)
In the article specifial features of one of the characteristic collective information consumers in sphere of management Ministry of Higher and Special Secondary Education of Lithuanian SSR – are described. An indirect method of research of information needs of the Ministry is used. Methods of analysis of documents about functional distribution and choice of solution are prepared. Information needs of 11 subsystems of first and second levels of the Ministry, consisting of 80 generalized and 248 detalized topics are determined. Intensity of individual information needs and their distribution in time are determined on the base of analysis of the most important solutions. The received data enable to expleyt experimentally the information system of the Ministry of Higher and Special Secondary Education of Lithuanian SSR.